Surface quality characterization of thin Nb films for superconducting radiofrequency cavities. (1st July 2022) - Ries, R; Seiler, E; Gömöry, F; Medvids, A; Onufrijevs, P; Pira, C; Chyhyrynets, E; Malyshev, O B; Valizadeh, R
Abstract: Superconducting radiofrequency (SRF) cavities are vital components of particle accelerators nowadays. In order to minimise the energy dissipation, a perfect inner surface of the cavity, hindering the penetration of magnetic field, is required. In this work, we investigated ten planar samples differing in the surface quality of Nb film deposited on Cu substrate, and as a consequence exhibiting various levels of the first entry field, H en, at which the magnetic field starts to enter the film. The observed surface defects are categorised as hills, pits and cracks. For a practical range of dimensions of these features, the factor β, characterising the local magnetic field enhancement, was calculated by the numerical finite-element simulations. It is expected that the local field enhancement causes a premature penetration of the magnetic field, thus lowering H en . Then, for each investigated sample, the range of β values characterising defect type that cause the highest field enhancement, is identified and compared with the H en fields. We have found that the H en of the samples that contain multiple types of the surface features is indeed limited by those defects that cause the highest field enhancement. The H en vs β dependence has shown a good match with linear fit for the set of investigated samples. Thus, the main result is that the local magnetic field enhancement, computed in a straightforward way for the most significant defects, is a strong indicator of the surface quality that is relevant for the superconducting film intended for SRF cavity application.